Flood damage, vulnerability and risk perception - challenges for flood damage research - Frank Messner; Volker Meyer (UFZ-Umweltforschungszentrum Leipzig-Halle, 2005)
The current state-of-the-art in flood damage analysis mainly focuses on the economic evaluation of tangible flood effects. It is contended in this discussion paper that important economic, social and ecological aspects of flood-related vulnerabilities are neglected. It is a challenge for flood research to develop a wider perspective for flood damage evaluation.
Keywords: 330; Flood damage analysis; flood vulnerability; risk perception; cost-benefit analysis; integrated assessment